When Raccoons Fall Through Your Ceiling : the Handbook for Coexisting with Wildlife. - Lopez, Andrea Dawn (Practical Guide S., No. 3., 2002)
The paths of humans and wildlife cross all the time, and it is the aim of this handbook to make sure those paths cross as peacefully as possible. Andrea Dawn Lopez tackles a wide range of situations that occur when human and non-human worlds clash.